Incubation of alcohol craving as it naturally occurs in a developmentally diverse sample of dependent and nondependent drinkers. (14th July 2020) - Treloar Padovano, Hayley; Miranda, Robert
Abstract: Longer periods of abstinence are shown to enhance response to alcohol cues among alcohol‐dependent animals and humans, a phenomenon described as "incubation of craving." The present work examined the effects of days since last drink on general craving and alcohol‐cued craving as it occurs in daily life and explored whether effects were influenced by age and dependence. Three samples were combined to include 266 drinkers ranging in age from 14 to 67 years recruited from the community; about half (59.4%) met criteria for alcohol dependence. Drinkers used handheld electronic devices to rate their subjective alcohol craving (assessed as "urge to drink") and situational context (e.g., presence of visible alcohol cues) at nondrinking times in daily life, with days since last alcohol use culled from timeline follow‐back interviews and real‐world reports. Drinkers at the lower end of the age range in this sample reported greater intensification of craving with more days of continuous abstinence than drinkers at the upper end of the age range. Age was not related to incubation of cue‐elicited craving, in specific, however. For drinkers with dependence, craving when in the presence of visible alcohol cues intensified with more days of continuous abstinence, suggesting craving incubation. This study builds from important foundational work to demonstrate that incubation of cue‐elicited craving occurs in dependent drinkers and applies regardless of age. Inasmuch as craving is a motivational drive that maintains alcohol use, understanding factors that influence craving in daily life holds promise for improving clinical care. Abstract : Longer periods of abstinence enhance cue‐elicited craving in animal models of addiction, a phenomenon described as "incubation of craving." In the present study, 266 drinkers ages 14 to 67 (59.4% with alcohol dependence), reported their level of alcohol craving and the presence or absence of visible alcohol cues in the natural environment. Craving when in the presence of visible alcohol cues intensified with more days of continuous abstinence, specifically among drinkers with dependence, suggesting craving incubation.